Modification of nanocellulose by double-walled carbon nanotubes and graphite carbon nanopowder for sensor applications - Toomadj, Farshad (My University, 2011)
Electrically conductive nanocellulose films were prepared by immersion in dispersions of double walled carbon nanotubes or graphitized nanopowder. These solutions were prepared by using the surfactant cetyltrimethylammonium bromide (CTAB) under heating and stirring which were followed by short time sonications. Electrospun cellulose and bacterial cellulose were used as a backbone of these films. Controllable modification of cellulose with conductive agents was performed by treatment with their dispersions for 24 – 72 hours. In this project it has been showed that the conductivities of resulted films were changed depends on changing in type of modifying agent, type of cellulose which was used as a backbone, and immersion time. The best electrical conductivity of the resulting films are 0.395 S cm-1 for bacterial cellulose modified by double-walled carbon nanotube, 0.0086 S cm-1 for electrospun cellulose modified by double-walled carbon nanotube and 0.334 for bacterial cellulose modified by graphitized nanopowder. These results are higher or comparable to previously reported results. Some methods have been employed to study the electrical conductivity behavior of samples. The electrical conductance of the films displays a high sensitivity to strain when tensile stress is applied.
Keywords: Materialvetenskap; Nanovetenskap och nanoteknik; Annan kemi; Övrig elektroteknik, elektronik och fotonik; Materials Science; Nanoscience & Nanotechnology; Other Chemistry Topics; Other electrical engineering, electronics and photonics